Modified and unmodified low-cost iron-containing solid wastes as adsorbents for efficient removal of As(III) and As(V) from mine water - Iakovleva, E.; Maydannik, P.; Ivanova, T.; Sillanpää, M.; Tang, W.; Mäkilä, E.; Salonen, J.; Gubal, A.; Ganeev, A.; Kamwilaisak, K.; Wang, Shaobin (Elsevier, 2016)
© 2016 Elsevier LtdSulphate tailings and iron sand – industrial solid wastes containing iron oxide/hydroxides – were investigated as potential adsorbents for arsenic removal from water. Two effective methods of surface modification by NaOH treatment and atomic layer deposition of TiO2 and Al2O3 thin films were used for increasing As(III) and As(V) removal capacities of both adsorbents. The structure and surface area of the materials were characterised by scanning electron microscopy, middle infrared region spectroscopy, energy dispersive X-ray spectroscopy, and nitrogen adsorption. The iron sand waste was capable of binding significant amounts of As(III) and As(V) from synthetic solutions and wastewater. The sulphate tailings also showed a high adsorption capacity. Adsorption kinetics showed that equilibrium was reached within 240 min and fit to a pseudo second-order model with correlation coefficients greater than 0.99. Adsorption capacity was at the highest value at a solution pH range of 6–8. The Langmuir and Toth models can be used to fit the adsorption isotherms. The research showed that the proposed solid wastes can be successfully used for the adsorption of As(III) and As(V).